2013
DOI: 10.1111/sjop.12092
|View full text |Cite
|
Sign up to set email alerts
|

The prospective relationship between role stressors and new cases of self‐reported workplace bullying

Abstract: In line with the "Work environment hypothesis," role stressors have been proposed as important antecedents of bullying in the workplace. Only a few longitudinal studies on the relationship between role stressors and bullying exist, however, and earlier studies have largely been cross-sectional. The aim of the present prospective study was to determine whether role stressors at baseline predict new cases of workplace bullying at follow-up. A total of 2,835 Norwegian employees participated at both baseline and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 34 publications
6
47
0
2
Order By: Relevance
“…However, these factors may interact in complex causal processes influencing mental distress. For instance, non-supportive leadership [58], role conflict [58], [59], and role ambiguity [59] have been related to increased prevalence of workplace bullying. In the present study, role conflict, supportive leadership, and bullying were predictors of mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…However, these factors may interact in complex causal processes influencing mental distress. For instance, non-supportive leadership [58], role conflict [58], [59], and role ambiguity [59] have been related to increased prevalence of workplace bullying. In the present study, role conflict, supportive leadership, and bullying were predictors of mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, workplaces with higher social cohesion/social capital are associated with a greater exchange of social support between coworkers, as well as between supervisors and subordinates. Social support can take the form of the exchange of health-relevant information, and mutual respect between workers (as in the absence of discrimination, bullying and harassment) 27. However, in addition to social support, workplace social capital might promote health via other pathways—such as the ability to enforce healthy norms (such as safety climate).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kilroy et al (2016) found that HPWPs decreased role conflict and role clarity among health care professionals. Role stressors, both role ambiguity and role conflict, have been shown to be associated with a higher risk of bullying (Reknes, Einarsen, Knardahl, & Lau, 2014). In fact, of all the work environment characteristics, role conflict has been found to be one of the strongest predictors of workplace bullying and harassment (Bowling & Beehr, 2006;Hauge et al, 2007).…”
Section: Workplace Bullying Risk Factors and The Potential Role Ofmentioning
confidence: 99%
“…The former suggests that HR practices need to be designed in ways that clarify expectations and empower employees to proactively define their own role within the organization (cf. Evans & Davis, 2005), because lower levels of role conflict are associated with less bullying (e.g., Hauge et al, 2007;Reknes et al, 2014).…”
Section: Practical Implicationsmentioning
confidence: 99%